-4(x 1)-3= -3(x-4) is an algebra 1 question. I am having a hard time understanding it

Algebra
Tutor: None Selected Time limit: 1 Day

Oct 7th, 2015

Hello!

I suppose that the missed sign is "+":

-4(x+1)-3= -3(x-4).

First, open the parentheses using the distributive law:
-4x - 4 - 3 = -3x + 12, or
-4x - 7 = -3x + 12.
Now move terms with x to the right and without x to the left:
-7 - 12 = -3x + 4x, or
-19 = x.
The answer: x = -19.

Please ask if something is unclear.
Oct 7th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Oct 7th, 2015
...
Oct 7th, 2015
Dec 4th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer